2016
DOI: 10.4193/rhin15.157
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of chronic rhinosinusitis in South Korea according to diagnostic criteria

Abstract: The prevalence and risk factors of CRS were quite different from each other according to the different criteria, even in the same population. Therefore, it would be important to consider what specific diagnostic criteria have been adopted in the studies comparing the prevalence of CRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 17 publications
3
21
0
1
Order By: Relevance
“…The 2008–2012 KNHANES also showed that the prevalence of had decreasing pattern by aging [ 30 ]. The prevalence of RS was 7.8% in our present study, which is similar to those in other studies of the general Korean population (range = 6.95–10.78%) [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The 2008–2012 KNHANES also showed that the prevalence of had decreasing pattern by aging [ 30 ]. The prevalence of RS was 7.8% in our present study, which is similar to those in other studies of the general Korean population (range = 6.95–10.78%) [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…We found that 40.2% of subjects with RS also had AR. In two Korean population-based studies, the proportions of patients with comorbid AR and RS were 33.6% [ 32 ] and 18.4% [ 29 ], respectively. Several studies have found that atopy was more prevalent in CRS patients, and positive skin test results were reported in 50–84% of such patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] A previous Korean population study found that the prevalence of symptom-based CRS was 10.8%, but it was 1.2% when diagnosed by symptoms plus endoscopy. [ 29 ] In the present study, similar to the previous study, the prevalence of CRS with/without nasal polyps was 1.2% (1,019/88,170). It is possible that bias was minimized by selecting patients who underwent head and neck computed tomography evaluations.…”
Section: Discussionsupporting
confidence: 91%
“…However, the definition of rhinosinusitis is often based only on symptoms in epidemiological studies. Kim et al reported that the prevalence of chronic rhinosinusitis (CRS) was 10.8% when diagnosed by symptoms only; however, it was 1.2% when diagnosed by symptoms and endoscopy in a Korean population [ 2 ].…”
Section: Introductionmentioning
confidence: 99%